Portable air cleaners should be at the forefront of the public health response to landscape fire smoke. Issue 1 (December 2016) - Barn, Prabjit; Elliott, Catherine; Allen, Ryan; Kosatsky, Tom; Rideout, Karen; Henderson, Sarah
Abstract Landscape fires can produce large quantities of smoke that degrade air quality in both remote and urban communities. Smoke from these fires is a complex mixture of fine particulate matter and gases, exposure to which is associated with increased respiratory and cardiovascular morbidity and mortality. The public health response to short-lived smoke events typically advises people to remain indoors with windows and doors closed, but does not emphasize the use of portable air cleaners (PAC) to create private or public clean air shelters. High efficiency particulate air filters and electrostatic precipitators can lower indoor concentrations of fine particulate matter and improve respiratory and cardiovascular outcomes. We argue that PACs should be at the forefront of the public health response to landscape fire smoke events.